Vibration–Collision Coupling Modeling in Grape Clusters for Non-Damage Harvesting Operations - Baocheng Xu; Jizhan Liu; Yucheng Jin; Kaiyu Yang; Shengyi Zhao; Yun Peng (Agriculture)
In the table grape production process, issues such as berry detachment and damage caused by cluster vibrations and berry collisions are significant challenges. To investigate the underlying mechanisms and dynamics of these phenomena, a vibration–collision coupling method for table grape clusters was developed. Based on the vibration model of a grape cluster, the smallest vibration–collision coupling unit—referred to as the dual-twig–berry system—was proposed. This system was described using a “(viscoelastic hinge)–(rigid bar)–(flexible sphere)–(viscoelastic link)” model. The dynamic vibration–collision coupling equation of the dual-twig–berry system was derived by incorporating expressions for the viscoelastic vibration of the twigs, viscoelastic collision of the berries, and a generalized collision force (based on the Kelvin model) into the framework of the Lagrange equation. A computational-simulation method for solving this dynamic vibration–collision coupling equation was also developed. The simulation results revealed that the vibration–collision coupling pattern exhibited a shorter vibration period, smaller vibration amplitude, and higher vibration frequency compared to the vibration pattern without coupling. A reduction in vibration amplitude mitigates berry detachment caused by excessive instantaneous loads. However, the increase in vibration frequency exacerbates berry detachment due to fatigue and causes varying degrees of berry damage. This study provides a theoretical foundation for understanding the mechanisms of berry detachment and damage, offering valuable insights for mitigating these issues in table grape production.